Social maturity among obese children in Surakarta, Indonesia - Endang Dewi Lestari; Dwi Hidayah; Suci Murti Karini (Indonesian Pediatric Society, 2006)
Background Although it is clear that childhood obesity has asso-ciation with many aspects included social aspect, the social matu-rity aspect on childhood obesity is scarcely found.Objective To examine the prevalence of social maturity and thepossible associated factors among obese children.Methods A cross sectional study was conducted from January toFebruary 2005. Twenty percent of elementary schools in every sub-district were randomly selected. All obese children from selectedschools were recruited to the study after obtaining the informedconsent. Criteria of obesity in children was based on BMI eâ€95 thpercentile according to age and sex. Social maturity was measuredusing Vineland Social Maturity Scale, which consisted of 8 catego-ries, i.e., self-help general, self-help eating, self-help dressing, self-direction, occupation, communication, locomotion, and socializa-tion. Social maturity score was determined using age group. Thetotal score was divided into two categories i.e. immature and ma-ture. Possible associated factors with the social maturity such asgender, maternal education less than 9 years, being held back aclass, and parental guidance by step mother were analyzed usingSPSS 10.0 for Windows.Results There were 158 obese children recruited in the study. Theprevalence of social immaturity was 32.5%. The odds ratio (OR)for parental guidance by single parent or others was 2.32 (95%CI1.01;5.31); OR for intelligence was 3.93 (95%CI 1.42;10.89); ORfor male was 2.41 (95%CI 1.08;5.38) and OR for maternal educa-tion less than 9 years was 1.22 (95%CI 0.61;2.41). Multivariateregression, analysis showed significant association between gen-der (for male OR=2.44; 95%CI 1.06;5.58) and intelligence(OR=3.31; 95%CI 1.12;9.84) with social maturity.Conclusion The prevalence of social maturity in obese children ishigh. The factors associated with social maturity among obese chil-dren are the history of had ever been held back a class and male.Further investigation is needed to find out the understanding ofspecific influence of social maturity in the prevalence of obesity.